The effect of light intensity on image quality in endoscopic ear surgery. (11th June 2018) - McCallum, R.; McColl, J.; Iyer, A.
Abstract : Objectives: Endoscopic ear surgery is a rapidly developing field with many advantages. But endoscopes can reach temperatures of over 110°C at the tip, raising safety concerns. Reducing the intensity of the light source reduces temperatures produced. However, quality of images at lower light intensities has not yet been studied. We set out to study the effect of light intensity on image quality in EES. Design: Prospective study of patients undergoing EES from April to October 2016. Consecutive images of the same operative field at 10%, 30%, 50% and 100% light intensities were taken. Eight international experts were asked to each evaluate 100 anonymised, randomised images. Setting: District General Hospital. Participants: Twenty patients. Main Outcome Measures: Images were evaluated on a 5‐point Likert scale (1 = significantly worse than average; 5 = significantly better than average) for detail of anatomy; colour contrast; overall quality; and suitability for operating. Results: Mean scores for photographs at 10%, 30%, 50% and 100% light intensity were 3.22 (SD 0.93), 3.15 (SD 0.84), 3.08 (SD 0.88) and 3.10 (SD 0.86), respectively. In ANOVA models for the scores on each of the scales (anatomy, colour contrast, overall quality and suitability for operating), the effects of rater and patient were highly significant ( P  < .0005) but light intensity was non‐significant ( P  = .34, .32, .21, .15, respectively). Conclusion: Images taken during surgery by our endoscope and operative camera have no loss of quality when taken at lower light intensities. We recommend the surgeon considers use of lower light intensities in endoscopic ear surgery.